WORKLOAD, REPETITIVE WRIST MOVEMENTS, YEARS OF SERVICE WITH CARPAL TUNNEL SYNDROME - Ratna Kurnia Sari; Diki Bima Prasetio; Ratih Sari Wardani (Jurnal Riset Kesehatan, 2020)
Carpal Tunnel Syndrome (CTS) is an occupational disease caused by disruption of the hand position which is constantly and is often associated with activities that use the hands for a long time can affect nerves, blood supply to the hands and wrists. This study aims to determine the relationship between workload, repetitive wrist movements and work time with carpal tunnel syndrome in cantel eyelash workers. Type of research is observational with cross-sectional approach. The sample in study were 50 eyelash workers who were part of the cantel. The results of this study are there is no relationship between workload and the incidence of CTS (p=1.000), there is a relationship between repetitive wrist movements with the incidence of CTS (p=0.031) and There is a relationship between years of service and the incidence of CTS (p=0.007). The conclusion is repetitive wrist movements performed by workers during years of work are a risk factor for carpal tunnel syndrome. So that to reduce this risk, it is necessary to stretch your hands before working, every two hours of work and finish working.